Background to the Arrival of the Dutch, VOC, Dutch East Indies - Basri, Muhammad; Ayu, Sara Ningtya; Nabilla, Ghina; Berutu, Syanti Luara (EDUCTUM: Journal Research, 2024)
The arrival of the Dutch to Indonesia was initially motivated by the ship's aim of searching for spices, and the first Dutch ships entered the waters of the Indonesian archipelago in 1596, after the arrival of the Portuguese and Spanish. The history of the arrival of the Dutch to Indonesia includes several political events and ocean exploration carried out by Europeans. In 1602, the VOC (Vereenigde Oost-Indische Compagnie) was founded by the Dutch government with the aim of controlling and trading the abundant spices in the Asian region. VOC became the first multinational company in the world by introducing a trading system and controlling ports and kingdoms in Indonesia. At that time, the Netherlands experienced important policies such as the right of expatriation, which guaranteed the right to cut and burn spices, and contingenten, which was a policy of taxpayers who had to guarantee a predetermined nominal amount. In running its government, the VOC experienced various economic policies aimed at controlling trade and supervising monopolies. However, several factors such as competition between Dutch traders, intense trade competition with England and France, and rampant corrupt practices influenced the VOC's success. In 1799, the VOC was officially declared bankrupt, and its assets were taken over by the Dutch government. In the context of colonial rule, the Netherlands experienced important policies such as expatriation, contingent and church rights. Dutch colonial buildings in Indonesia developed with architecture that reflected local culture, and churches were one of the buildings standing at that time